Ecotoxicity of HfO2 and SiO2 Nanoparticles on Bacteria (anaerobic methane Archaea); Yeast (Candida albicans) and Biodegradability Tests - Delia Teresa Sponza; Nefise Erdinçmer (Annals of Environmental Science and Toxicology - Peertechz Publications, 2020)
The applications nano-metal oxides (NMOs) are used in very common in industrial and consumer products because of the advantages of nanotechnology. The use of these NMOs cause the release of NMOs throughout the life cycle of nanoproducts to air, soil, water, and sediments. Knowledge of potential toxicity of nanoparticles to organisms is limited. To determine the toxicological effects of nano-HfO2  and  nano-SiO2;  on  the anaerobic methane Archaea from bacteria and to Candida albicans from yeast, some toxicity analyses were performed to detect the  EC50 values (nanoparticle concentration inhibiting 50 % of the organisms). These values were calculated from the inhibitions of NMOs versus exposure time (24, 48 hours and 28 days). Anaerobic methane Archaea bacteria are very sensitive to nano-SiO2. While the inhibiton rate is 100 % for nano-SiO2, nano-HfO2 is less toxic to anaerobic bacteria because of the 13.97 % inhibiton rate after 48 h. Compare to nano-HfO2, the EC50 value of nano-SiO2 were low and showed high toxicity towards to C.albicans (24 h EC50=119.68 mg/L; 48 h EC50=98.06 mg/L). From the 28 days biodegradabilty tests of NMOs, it was found that the percantage of removal efficiencies are 11.2 % and 55.9 for 100 mg/L nano-HfO2 and nano-SiO2, respectively after 28 days.